2010
DOI: 10.1051/forest/2009112
|View full text |Cite
|
Sign up to set email alerts
|

Mortality of silver fir and Norway Spruce in the Western Alps — a semi-parametric approach combining size-dependent and growth-dependent mortality

Abstract: Abstract• Question: Tree mortality can be modeled using two complementary covariates, tree size and tree growth. Tree growth is an integrative measure of tree vitality while tree diameter is a good index of sensitivity to disturbances and can be considered as a proxy for tree age which may indicate senescence. Few mortality models integrate both covariates because classical model calibration requires large permanent plot data-sets which are rare. How then can we calibrate a multivariate mortality model includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
2

Year Published

2011
2011
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 58 publications
2
23
2
Order By: Relevance
“…As we assume that the limiting basal area for growth is 60 m 2 , we assume that this state also induces a 5 % yearly mortality, which is compatible with previous observations in mountain forests (Vieilledent et al 2010a), and thus gives us z = 5 %/60 = 0.008; and • the potential growth parameter b is set (by simple calibration method) to 0.75 in order to obtain a reasonable forest structure as observed in the Vercors (Redon et al (2014) and unpublished data): for a mean removal of 6 m 3 year -1 ha -1 , we have about a 25 m 2 basal area in stratum 1 and a 5 m 2 basal area in stratum 2.…”
Section: Setting the Parameter Values Of The Viability Problemsupporting
confidence: 67%
See 1 more Smart Citation
“…As we assume that the limiting basal area for growth is 60 m 2 , we assume that this state also induces a 5 % yearly mortality, which is compatible with previous observations in mountain forests (Vieilledent et al 2010a), and thus gives us z = 5 %/60 = 0.008; and • the potential growth parameter b is set (by simple calibration method) to 0.75 in order to obtain a reasonable forest structure as observed in the Vercors (Redon et al (2014) and unpublished data): for a mean removal of 6 m 3 year -1 ha -1 , we have about a 25 m 2 basal area in stratum 1 and a 5 m 2 basal area in stratum 2.…”
Section: Setting the Parameter Values Of The Viability Problemsupporting
confidence: 67%
“…Green [80 %. Where there is no color, the states are not viable, which puts local flexibility at 0 ðd 1 ; h 1 ; m 1 Þ 0.16 (0.45,25,2.29)(Vieilledent et al 2010a) and(Vallet et al 2006) for computations of m 1 and m 2 g 2 ðd 2 ; h 2 ;…”
mentioning
confidence: 99%
“…Our findings underscore that tree decline is driven by the individual growth sensitivity. Such intra-specific variability may have deep consequences for tree growth and survival leading to the selective mortality of the most sensitive trees (Clark 2003) as has been evidenced in silver fir (Vieilledent et al 2010;Rathgeber et al 2011). Future studies on forest decline should deal with the consideration and quantification of intra-specific variability at the tree level considering both local and regional scales.…”
Section: Discussionmentioning
confidence: 97%
“…Radial growth, used here as a proxy of whole plant carbon gain (Litton et al 2007), may be used to identify those trees with the highest probabilities of severe defoliation, decline and death (Wunder et al 2008;Vieilledent et al 2010;Carnicer et al 2011). Several studies have shown that tree defoliation, mean radial growth and radial growth trends are, to some extent, inversely related (Buchman et al 1983;Kobe and Coates 1997;Wyckoff and Clark 2000;van Mantgem et al 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, strong competitive abilities of A. alba were found in the western Alps. Silver fir was more resistant to low growth and had lower mortality in comparison with Picea abies (Vieilledent et al 2010). However, the decline of Abies alba in natural ecosystems is more often observed (Thomas et al 2002;Camarero et al 2011;Ficko et al 2011;Klopcic and Boncina 2011).…”
Section: Discussionmentioning
confidence: 95%